(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This study examines the relationship between youth unemployment and criminal activities in Calabar Metropolis, Cross River State, Nigeria. It explores the link between unemployment and youth involvement in property crimes, violent crimes, and cybercrimes. The study adopts Robert Merton’s structural strain theory and employs a correlational research design. A sample of 800 respondents was selected using Taro Yamane’s formula, and data were collected through a structured questionnaire. Multistage sampling, including stratified, simple random, systematic, and purposive techniques, was applied. Hypotheses were tested using Pearson’s correlation at a 0.05 significance level. Findings reveal a significant relationship between youth unemployment and property crime, violent crime, and cybercrime. The study concludes that high unemployment drives youth criminality and recommends legislative efforts to boost agriculture and enhance rehabilitation programs equipping offenders with entrepreneurial skills.